1991
DOI: 10.1111/j.1469-8137.1991.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf demography and the seasonal internal cycling of nitrogen in sycamore (Acer pseudoplatanus L.) seedlings in relation to nitrogen supply

Abstract: SUMMARYThe dynamics of tbe seasonal internal cycling of nitrogen (N) in Acer psexidoplatonus were studied in relation to N supply and leaf demography. Trees were grown in sand culture, and throughout 1988, supplied with either 1-0 mol N m"' (Low N) or 6-0 mol N m •' (High N), labelled with '-"'N to 5-0 atom %, in order to precondition their growth and capacity for N storage over the winter period. In 1989, the initial spring growth of leaves was independent of the current N supply at either 1-0 or 6-0 mol N n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 28 publications
(32 reference statements)
12
95
1
1
Order By: Relevance
“…This compartment could be defined as a storage compartment in young sessile oaks. Such an observation has been already reported for oaks of the same pole stand (Gilson et al, 2014), and similar findings were reported for field-grown adult peach trees by Tagliavini et al (1997), being typical of other young deciduous trees (Millard and Proe, 1991;Salaün et al, 2005;Tromp and Ovaa, 1979;Wendler and Millard, 1996). On this date (end of September), branches and coarse roots could also have contributed significantly to N storage, as previously described (Bazot et al, 2013).…”
Section: N Dynamics In Soil-tree Systems During the First Leafy Seasonsupporting
confidence: 74%
“…This compartment could be defined as a storage compartment in young sessile oaks. Such an observation has been already reported for oaks of the same pole stand (Gilson et al, 2014), and similar findings were reported for field-grown adult peach trees by Tagliavini et al (1997), being typical of other young deciduous trees (Millard and Proe, 1991;Salaün et al, 2005;Tromp and Ovaa, 1979;Wendler and Millard, 1996). On this date (end of September), branches and coarse roots could also have contributed significantly to N storage, as previously described (Bazot et al, 2013).…”
Section: N Dynamics In Soil-tree Systems During the First Leafy Seasonsupporting
confidence: 74%
“…The experiment took place outdoors at the Instituto Superior de Agronomia (Lisbon, Portugal). Plants were regularly watered and, twice a week, fertilised with a complete nutrient solution (6 mol m -3 N in the form NH 4 NO 3 ) as detailed in [17]. Spring growth flush began in March and lasted until July 1997.…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 99%
“…Each week, 1000 cm$ of nutrient solution containing 6n0, 1n33, 1n25, 0n75, 2n0 and 1n25 moles m −$ of N, P, K, Mg, Ca and S, respectively, with 20, 10, 5, 1 and 1 mmoles m −$ of Fe, Mn, B, Zn and Cu, respectively, was applied to each tree (Millard & Proe, 1991). Additional deionized water was applied as required during summer.…”
Section: Experimental Designmentioning
confidence: 99%